2022
DOI: 10.1186/s12890-021-01811-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the anti-fibrotics for the treatment of idiopathic pulmonary fibrosis in the United States

Abstract: Background The anti-fibrotic medications nintedanib and pirfenidone were approved in the United States for use in patients with idiopathic pulmonary fibrosis several years ago. While there is a growing body of evidence surrounding their clinical effectiveness, these medications are quite expensive and no prior cost-effectiveness analysis has been performed in the United States. Methods A previously published Markov model performed in the United Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition, Dempsey et al. (2021) 14 suggested that nintedanib and pirfenidone were not considered cost-effective compared with symptom management for IPF in the United States due to their high price.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dempsey et al. (2021) 14 suggested that nintedanib and pirfenidone were not considered cost-effective compared with symptom management for IPF in the United States due to their high price.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the costs on drug therapies for IPF are uneven, and some couple with high prices. 14 Due to the irreversible nature of IPF, as well as the multitude of acute exacerbation and hospitalisation that accompany it, a substantial economic burden has been imposed on individuals and overall healthcare resources. 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“… 45 , 46 FVC% predicted disutilities were sourced from the literature. 47 The utilities were applied based on the scores for each patient in the cycle and were additive. Disutilities were applied to the no response state, assuming progressive disease.…”
Section: Methodsmentioning
confidence: 99%
“…The approval of Nintedanib and Pirfenidone was indeed a breakthrough in treating fibrosis. However, there are currently no generic alternatives, creating a significant financial barrier for use of these therapies in Europe and the United States [143] [144]. Additionally, research into reprogramming, particularly for cardiac fibrosis, is progressing towards clinical application.…”
Section: Future Direction and Conclusionmentioning
confidence: 99%